Dari Self-Actualization ke Self-Transcendence: Kritik Humanistik atas Reduksi Nilai Transendental dan Rekonstruksi Spirit Transformasi Sosial dalam Perspektif Abraham Maslow dan Tasawuf - Ferlita Fhathiannisa Mumthahannah; Anjani Nadia Putri; Nia Nur Laily; Najmuddin Arif Kurniawan; Ali Hasan Siswanto (Indo Publishing, 2026)
This article stems from the epistemological crisis in modern science, which tends to reduce transcendental values to an empirical-psychological framework, thus losing their ontological and axiological dimensions in human life. Although Abraham Maslow's thinking has shifted psychology's orientation from self-actualization to self-transcendence, contemporary studies indicate a research gap in the form of minimal conceptual integration between humanistic-existential psychology and the Sufi tradition, as well as the absence of an operational methodological model for applying transcendental values as a basis for social transformation.This article uses an I ntegrative theoretical approach between Maslow's humanistic-existential psychology and Sufi metaphysics, using qualitative research methods based on conceptual-philosophical analysis and critical hermeneutics of classical and contemporary texts. The main argument put forward is that transcendental values must be reconstructed as epistemic realities and existential practices that not only shape individual consciousness but also function as ethical energy in social transformation. This study offers a new framework, the Transcendental-Humanistic Sufism Framework, and the Experiential-Reflective Transcendental Praxis methodological model, which bridges spiritual experience, existential reflection, and social action. The article's scientific contribution lies in its effort to reposition transcendental values as the core of developing a humanistic and transformative science, opening new horizons for the integration of modern psychology and Sufism in a global scientific context.